Risk factors of early death in pediatric hemophagocytic lymphohistocytosis: Retrospective cohort study - Zhang, Lijun; Dai, Lei; Li, Deyuan (Frontiers in Pediatrics, 2022)
Background: Hemophagocytic lymphocytosis (HLH) is a rare life-threatening hyperinflammatory syndrome in which early mortality remains high in patients with HLH. Methods: We retrospectively collected the medical records of all pediatric patients diagnosed with HLH at the West China Second Hospital of Sichuan University between January 2014 and December 2020. Collect demographic, laboratory, clinical, genetic profiles, treatment information and perform statistical analysis from records. Risk factors for death 30 days after admission were evaluated using a multivariable logistic regression model. Results: A total of 110 pediatric HLH patients were enrolled. The median age of patients was 44 months (IQR 23-100.5) and 62 (56.4%) in males. The 30-day mortality rate for admission to this cohort was 34 (30.9%). Multivariate logistic regression analysis showed that heart failure (OR=13.389, 95% CI 1.671-107.256, p=0.015) and hypoproteinemia (OR=4.841, 95% CI 1.282-18.288, p=0.020) were associated with increased early mortality in children with HLH. Conclusions: These identified risk factors may help clinicians stratify patients with HLH and develop targeted treatment strategies. More research is needed to explore the best treatment strategies for patients with HLH to reduce early mortality in patients with HLH.